Swine Leukocyte Antigen Class II Is a Xenoantigen. Issue 2 (February 2018) - Ladowski, Joseph M.; Reyes, Luz M.; Martens, Gregory R.; Butler, James R.; Wang, Zheng-Yu; Eckhoff, Devin E.; Tector, Matthew; Tector, A. Joseph
Abstract : Background: Over 130 000 patients in the United States alone need a lifesaving organ transplant. Genetically modified porcine organs could resolve the donor organ shortage, but human xenoreactive antibodies destroy pig cells and are the major barrier to clinical application of xenotransplantation. The objective of this study was to determine whether waitlisted patients possess preformed antibodies to swine leukocyte antigen (SLA) class II, homologs of the class II HLA. Methods: Sera from people currently awaiting solid organ transplant were tested for IgG binding to class II SLA proteins when expressed on mammalian cells. Pig fibroblasts were made positive by transfection with the class II transactivator. As a second expression system, transgenes encoding the alpha and beta chains of class II SLA were transfected into human embryonic kidney cells. Results: Human sera containing IgG specific for class II HLA molecules exhibited greater binding to class II SLA positive cells than to SLA negative cells. Sera lacking antibodies against class II HLA showed no change in binding regardless of the presence of class II SLA. These antibodies could recognize either SLA-DR or SLA-DQ complexes. Conclusions: Class II SLA proteins may behave as xenoantigens for people with humoral immunity toward class II HLA molecules. Abstract : Using human embryonic cells transfected with class II SLA proteins, the authors demonstrate that patients with anti-class II HLA antibodies exhibit binding to these cells compared to none in SLA negative cells, suggesting that class II SLA proteins may serve as xenoantigens.